Effect of pruning height on the architecture of plants of camu camu (Myrciaria dubia HBK Mc Vaugh) in the experimental station of IIAP, Ucayali, Peru. - Abanto, Carlos (2011)
In order to evaluate the response camu camu’s plants in plantations initial undergoing training pruning, an experiment was installed in EE - IIAP-Ucayali, under a design randomized complete block, with 3 replications, making use of 20 plants per experimental unit. The pruning treatments were performing at different heights from the base of the stem, it was considered T0 [witness without pruning], T1 [pruning to 10 cm from the base], T2 [pruning to 20 cm from the base] and T3 [pruning to 40 cm from the base] in plants of known provenance. The investigation was directed to evaluate the number of shoots, shoot growth, plant height, basal diameter, crown diameter and number of branches. After of 9 months of evaluation was found significant differences between the variables except in top diameter. In the variable Height, treatment T0 [witness without pruning] outstanding because they were not pruned, among the remaining treatments has similarly behaved, surpassing the control treatment by 267 %. In addition to this, the basal diameter was found that T1 [pruning to 10 cm from the base] has a better performed with an average value of 1.96 cm compared with the control (1.7cm). The pruning had a positive influence in the number of branches, with an average of 13.4 branches compared with T0 that get 3.1 branches on average, its shows that the pruning can increased up the production of branches to 432.3%.